Mechanically deboned poultry meat and its role in rational and efficient use of raw materials - V. V. Gushchin (Теория и практика переработки мяса)
The growth in poultry meat production is a worldwide trend. Industrial poultry meat processing is also developing with production of a wide range of products. The technology of mechanical deboning of poultry meat and carcass parts is widely used in complex non-waste production. Mechanically deboned poultry meat (MDPM) is believed to be of inferior quality and its use is restricted by certain rules in different countries of the world. At the same time, hand separated meat is accepted as conventional meat and is not subjected to any restrictions. Over the last decades, the technology and equipment have been created that allow approximating MDPM to the category “meat” in terms of quality characteristics and reducing risks in its use upon reduction of pressure in the process of its production. However, costs of new equipment that enables producing a product with higher quality do not provide the expected efficiency, and a positive effect will be achieved only in the case of clear legal solutions regarding separation of MDPM types and methods of their classification and identification. The volume of scientific publications concerning a solution to this problematic theme is significant and scientists from many countries search for approaches to its realization differently. The difficulty in finding a solution is caused by the multifaceted nature of the problem, the character of non-standardized raw materials, a type of equipment being used to obtain different MDPM types, and various methods of investigations. Nevertheless, the performed studies create conditions for improvement of the approach to classification of different MDPM types by the production method and maximum allowable threshold values of the main standardized parameters, assessment methods, detection of their characteristics and substantiation of terminology.